DEMOGRAPHIC DETERMINANTS OF BOND INVESTMENT BEHAVIOR: A MICRO-LEVEL STUDY OF RETAIL INVESTORS IN URBAN INDIA - Shah, Rani Niral; Sharma, Rita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the impact of demographic factors on bond investment behavior among retail investors in urban India, with a focus on Ahmedabad. Utilizing a qualitative review-based approach, the research analyzed 19 peer-reviewed papers from Scopus and Web of Science out of a total of 31 initially identified studies. The objective was to understand how key demographic variables—specifically age, education, and income—influence investment decisions related to bonds. The findings indicate that while age and education levels do not significantly impact bond investment behavior, income shows a negative correlation. This suggests that individuals with higher income levels may prefer riskier or more diversified investment options, whereas middle-income groups may favor bonds for their relative safety and stability. The study reinforces the need for income-specific investment strategies and targeted financial literacy initiatives. Future research should include behavioral variables and extend to other urban and rural settings to build a more comprehensive framework of investor behavior in the Indian bond market.